PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA PERMAINAN UBUR-UBUR TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Soraya, Rahayu; Widya Ningtias, Sinta (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to determine the effect of the TGT learning model assisted by jellyfish game media on students' mathematical concept understanding abilities. This research was conducted at SDN 1 Balai Murni Jaya. This research is quantitative. This type of research uses pre-experimental design. The population in this study were all III class students consisting of 2 classes, namely class III A with 23 students and III B with 22 students. The sampling technique used purposive sampling. The sample in this study was III A with 23 students. The research design used was one group pretest and posttest. The data collection technique used in this study was a test. The test in this study was an essay test consisting of 8 questions. Based on the results of the hypothesis test using the paired sample t test, it can be seen that sig. (2-tailed) 0,000 <0,05. Thus, it can be concluded that there is an influence of the TGT learning model assisted by jellyfish game media on students' mathematical concept understanding abilities.